Cassava micro-regions in part of eastern Paraguay : An explanation of their form and comparative study of cassava production within some of them - Carter, Simon E. (International Center for Tropical Agriculture, 1986)
Cassava-specific microregions in part of eastern Paraguay, a climatically homogeneous area, were defined on the basis of secondary data and systematic random sampling of agricultural settlements. It was found that production is concentrated in the departments of Caaguazu, Itapua, San Pedro, Paraguari, Cordillera, Caazapa, Guaira, and Alto Parana. Rural per capita cassava consumption may be as high as 340 kg/yr and, despite an enormous production, problems have been identified, namely low soil fertility and large distances from the principal producing areas. Podzolic soils are mainly used for agricultural purposes and the limits of the microregions correspond to those of the areas of cultivated land. Agricultural production was differentiated on the basis of the principal cash crops grown, and differences in modal farm size were found. Cassava production in both older established settlements and newer colonies relies on traditional methods of land preparation, and harvesting is done as soon as possible when needed for subsistence. The variables and information used to define and describe the microregions are presented as a series of qualitative maps. The microregions are derived and mapped by overlaying these and comparing them manually. They are then described in a quick reference table. The interaction of a set of processes is stressed. The juxtaposition within the study area of areas of commercial cassava production and of areas where the crop is in short supply for subsistence is caused by and dependent upon varying market opportunities, problems of cash supply, labor shortages, soil fertility differences, and, of utmost importance, variable access to land. (AS (extract))